Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1530/rep.1.00464
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression for LH receptor, 17α-hydroxylase and StAR in the theca interna of preantral and early antral follicles in the bovine ovary

Abstract: The onset of gene expression for three proteins that play pivotal roles in theca interna function, namely the LH receptor (LH-R), cytochrome P450 17a-hydroxylase (17aOH) and the steroidogenic acute regulatory protein (StAR), was determined. Ovaries were obtained on day 9 of the oestrus cycle from mature synchronized dairy cows (n 5 5) and gene expression in preantral and antral follicles up to 4 mm in diameter was evaluated by in situ hybridization. LH-R and 17aOH mRNAs were observed first, in the theca intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
(40 reference statements)
3
13
1
1
Order By: Relevance
“…The early decline of the theca in these follicles is also consistent with reduced levels of thecal-derived androstenedione and testosterone in the follicular fluid compared with healthy and antral atretic follicles of the same size (Irving- Rodgers et al 2003b). It has been suggested that the basal atretic follicles develop from antral atretic follicles later in the process of atresia (Braw-Tal & Roth 2005); however, in the absence of an intermediate phenotype between antral and basal atresia as would be expected if one morphed into the other, together with the restriction of basal atresia to sizes !5 mm, and with two distinct phenotypes of healthy follicles that correspond to the same size ranges as for the two atretic phenotypes, it is more likely that these atretic follicle phenotypes are separate identities.…”
Section: Atresia Of Antral Follicles !5 MM In Diametersupporting
confidence: 58%
See 1 more Smart Citation
“…The early decline of the theca in these follicles is also consistent with reduced levels of thecal-derived androstenedione and testosterone in the follicular fluid compared with healthy and antral atretic follicles of the same size (Irving- Rodgers et al 2003b). It has been suggested that the basal atretic follicles develop from antral atretic follicles later in the process of atresia (Braw-Tal & Roth 2005); however, in the absence of an intermediate phenotype between antral and basal atresia as would be expected if one morphed into the other, together with the restriction of basal atresia to sizes !5 mm, and with two distinct phenotypes of healthy follicles that correspond to the same size ranges as for the two atretic phenotypes, it is more likely that these atretic follicle phenotypes are separate identities.…”
Section: Atresia Of Antral Follicles !5 MM In Diametersupporting
confidence: 58%
“…apoptosis as observed by DNA fragmentation or karyorrhexis. Examples of why this is important in follicles include the observation in bovine follicles of morphological dead pyknotic nuclei that can be TUNEL negative (Braw-Tal & Roth 2005) or not have DNA ladders by COMET (van Wezel et al 1999a). Using the latter two methods would not have identified all the dead cells.…”
Section: Which Cell(s) Die First Andmentioning
confidence: 99%
“…Se señaló que la atresia puede presentarse en cualquier momento del desarrollo oocitario (Ganias et al, 2008 ;Leonardo et al;Miranda et al), sin embargo en cautividad, lo más común es que aparezca en las fases de vitelogénesis y preovulatoria (Bromage & Cumaranatunga, 1988;LinaresCasenave et al, 2002;Miranda et al). En algunas especies, los factores más importantes que determinan el destino hacia la ovulación o la atresia de los folículos son la capacidad de respuesta a gonadotropinas, la capacidad de producir estradiol (Bao & Garverick, 1998;Braw-Tal & Roth, 2005;Garverick et al, 2002;Webb et al, 1999), la participación del sistema de factor de crecimiento insulinoide (IGF) (Rivera & Fortune, 2003a, 2003b) y el medio endocrinológico en el que se desarrollan (Webb et al).…”
Section: Resultados Y Discusiónunclassified
“…The rate-limiting step in steroidogenesis is the transport of cholesterol from the outer to the inner mitochondrial membrane, where it is converted to pregnenolone by cytochrome P450 cholesterol side chain cleavage complex. STAR, a mitochondrial phosphoprotein, has been identified as the critical cholesterol transport protein (14,75) and has been extensively studied across numerous species (10,83,85). In bovine follicles, the expression of STAR is restricted to the theca interna (3,73); however, it is acquired in granulosa cells following luteinization (3,61).…”
Section: Discussionmentioning
confidence: 99%